THE BENEFITS OF PROJECT-BASED LEARNING IN HIGH SCHOOL - Rameez Ahmad Bhat; Mr. Shabir Ahmad Dar (Journal of International Islamic Law, Human Right and Public Policy, 2023)
Project-Based Learning (PBL) has emerged as a transformative educational methodology in high school settings, addressing the limitations of traditional teaching methods by promoting active, student-centered learning. This paper explores the multifaceted benefits of PBL, drawing on a comprehensive review of existing literature. Key findings indicate that PBL significantly enhances student engagement by involving them in relevant and exciting tasks. It fosters the development of critical thinking and problem-solving skills through inquiry and real-world application. PBL has also been shown to improve academic achievement, with students often outperforming their peers on standardized tests. Additionally, PBL promotes collaboration and social skills, preparing students for teamwork in professional environments. The real-world preparedness offered by PBL equips students with practical experience and skills directly applicable to their future careers. Furthermore, PBL has the potential to promote equity and inclusivity in education by providing meaningful learning opportunities for all students. Despite challenges in implementation, such as the need for teacher training and new assessment methods, the benefits of PBL make it a promising approach for high school education. Future research should focus on longitudinal studies, experimental designs, and the integration of technology to further understand and enhance the effectiveness of PBL.